The Effect of Ascorbic Acid and Nicotinamide on Panton–Valentine Leukocidin Cytotoxicity: An Ex Vivo Study - Abdullah AlSaleh; Mohammed Shahid; Eman Farid; Khalid Bindayna (Toxins, 2023)
Background: Panton–Valentine Leukocidin sustains a strong cytotoxic activity, targeting immune cells and, consequently, perforating the plasma membrane and inducing cell death. The present study is aimed to examine the individual effect of ascorbic acid and nicotinamide on PVL cytotoxicity ex vivo, as well as their effect on granulocytes viability when treated with PVL. Materials and Methods: The PVL cytotoxicity assay was performed in triplicates using the commercial Cytotoxicity Detection Kit PLUS (LDH). LDH release was measured to determine cell damage and cell viability was measured via flow cytometry. Results and discussion: A clear reduction in PVL cytotoxicity was demonstrated (p < 0.001). Treatment with ascorbic acid at 5 mg/mL has shown a 3-fold reduction in PVL cytotoxicity; likewise, nicotinamide illustrated a 4-fold reduction in PVL cytotoxicity. Moreover, granulocytes’ viability after PVL treatment was maintained when incubated with 5 mg/mL of ascorbic acid and nicotinamide. Conclusions: our findings illustrated that ascorbic acid and nicotinamide exhibit an inhibitory effect on PVL cytotoxicity and promote cell viability, as the cytotoxic effect of the toxin is postulated to be neutralized by antioxidant incubation. Further investigations are needed to assess whether these antioxidants may be viable options in PVL cytotoxicity attenuation in PVL-associated diseases.